Effectiveness the Use of Audio Visual Media in Teaching Islamic Religious Education - Winarto Winarto; Ahmad Syahid; Fatimah Saguni (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2020)
This study examines the effectiveness of using audio visual as media in improving learning achievement of a Islamic Junior high schools. The study used qualitative methods with observation, interview and documentation as techniques for data collection. The results of this research shows that the use of audio visual media in enhancing the learning achievement of Islamic education at SMP Negeri 1 Palu was effective for several reasons: First, the use of audio-visual media can clarify the material that is taught, effectifying and functioning students’ sensory, both senses of sight and hearing in accordance with the nature of the characteristics of the material and subject matter that is taught. Second, gives stimulation, experiences and observations that is similar to students in the same time with the subject matter. Third, encourages students to be active in learning activity. By using the audio-visual media, we can also say that the PAI teachers have motivated the whole class to be actively included in the teaching learning proces. Fourth, audio-visual media is very effective in improving students’ interest and achievement in learning Islamic education. The supporting factors are the learning system thatt is used, the quality of teachers, the facilities and infrastructures, as well as the role of parents, communities and the agencies related. The factors that inhibit the effectiveness of using audio visual media are as follows: (1). Time allocation of learning, (2). Procurement of electricity. To overcome these problems we can use genset macine as temporary power, desain the material an media in accodane with time.